Kajian Etnozoologi Hewan yang Dikonsumsi pada Komunitas Orang Rimba di Taman Nasional Bukit Duabelas Kabupaten Sarolangun - Masyithah Masyithah; Bambang Hariyadi; Winda Dwi Kartika (BIO-SITE |Biologi dan Sains Terapan, 2016)
Bukit Duabelas National Park (TNBD) has become habitat for many kinds of flora and fauna as well as the area Orang Rimba’s odyssey. Orang Rimba have interacted with the environment for many years so that produce traditional knowledge about the use of animals that are consumed. The assessment of orang Rimba’s Local wisdom is very important to document their traditional knowledge which eroded by modernization and as an effort to preserve the animals consumed. This study aimed at investigating the species or animals for consumptions, describing orang rimba’s knowledge about wildlife utilization that can be consumd, hunting and how to treat animals that consumed. The study was conducted in a Orang Rimba community in TNBD Sarolangun that is used Snowball sampling to select the respondent. The data has been obtained by descriptive analysis. Techniques of data collection through in-depth interview, observation participative, documentation, and literature. These results indicate the Orang Rimba utilized 65 species of wild animals for consumptions, it consists; 13 species of mammals, 13 species of reptiles, 1 spesies of amphibian, 11 species of brids, 21 species of pisces, and 6 species of invertebrates. Orang Rimba have knowledge in utilizing animal consumption derived from ancestors and experience. This community utilizing animal protein needs through hunting activities. They combine hunting techniques with the equipment used to obtain hunted. The ravin processed in a simple way as boiled, baked, and disalay (smoked). moreover, This study suggested further necessary documentation regarding the use of animals that are consumed by the Orang Rimba in a different location and identification of animal species consumed. Keywords: ethnozoology, animal consumptions, Orang Rimba, TNBD